Fundamental limits and non-reciprocal approaches in non-Hermitian quantum sensing - Hoi-Kwan Lau (Nature Portfolio, 2018)
Non-Hermitian properties were proposed to be beneficial to sensing but it is not clear if this concept can be extended to the quantum regime. Here, Lau and Clerk self-consistently consider the impact of noise and measurement, and identify that nonreciprocity can improve sensing capabilities.